2021
DOI: 10.3390/jcs5060154
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Coupling Effect between Lignin and Polybutadiene Elastomer

Abstract: From an environmental and economic viewpoint, it is a win–win strategy to use materials obtained from renewable resources for the production of high-performance elastomer composites. Lignin, being a renewable biomass, was employed as a functional filler material to obtain an elastomer composite with a higher degree of mechanical performance. In the presence of a suitable coupling agent, an elevated temperature was preferred for the reactive mixing of lignin with polybutadiene rubber (BR). It is quite fascinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…It can be observed that the value of parameter a is twice the value of parameter b , making evident the good interaction between rubber and the reinforcing agent. As can be observed from Figure 4 , the combination of the high values of a with lower values of b leads to strong filler–EPDM rubber interactions [ 32 , 63 ], which is in agreement with the results obtained using the Kraus relation.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…It can be observed that the value of parameter a is twice the value of parameter b , making evident the good interaction between rubber and the reinforcing agent. As can be observed from Figure 4 , the combination of the high values of a with lower values of b leads to strong filler–EPDM rubber interactions [ 32 , 63 ], which is in agreement with the results obtained using the Kraus relation.…”
Section: Resultssupporting
confidence: 88%
“…The value of m can be obtained from the slope of V ro /V rf as a function of Φ/(1−Φ). The interaction constant between rubber and filler, C, can be estimated from Equation (9) [ 32 ]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, some examples are described in more detail in Table 8. Other studies also used BR [170][171][172], SR [173][174][175][176][177], EPDM [178,179] and EVA [180], as well as rubber blends such as NR/SBR [181][182][183][184][185][186], NR/NBR [187], NR/SBR/BR [188,189], NR/BR [190], NR/EVA [191] and SBR/NBR [192] as a matrix for lignocellulosic-based rubber composites.…”
Section: Synthetic Rubbersmentioning
confidence: 99%